Integration of Transcriptional and Post-transcriptional Analysis Revealed the Early Response Mechanism of Sugarcane to Cold Stress - Huang, Xing; Liang, Yongsheng; Zhang, Baoqing; Song, Xiupeng; Li, Yangrui; Qin, Zhengqiang; Li, Dewei; Chen, Rongfa; Zhou, Zhongfeng; Deng, Yuchi; Wei, Jiguang; Wu, Jianming (Frontiers in Genetics, 2021)
Cold stress causes major losses to sugarcane production, yet the precise molecular mechanisms that cause losses due to cold stress are not well-understood. To survey miRNAs and genes involved in cold tolerance, RNA-seq, miRNA-seq, and integration analyses were performed on Saccharum spontaneum. Results showed that a total of 118,015 genes and 6,034 of these differentially expressed genes (DEGs) were screened. Protein–protein interaction (PPI) analyses revealed that ABA signaling via protein phosphatase 2Cs was the most important signal transduction pathway and late embryogenesis abundant protein was the hub protein associated with adaptation to cold stress. Furthermore, a total of 856 miRNAs were identified in this study and 109 of them were differentially expressed in sugarcane responding to cold stress. Most importantly, the miRNA–gene regulatory networks suggested the complex post-transcriptional regulation in sugarcane under cold stress, including 10 miRNAs−42 genes, 16 miRNAs−70 genes, and three miRNAs−18 genes in CT vs. LT0.5, CT vs. LT1, and CT0.5 vs. LT1, respectively. Specifically, key regulators from 16 genes encoding laccase were targeted by novel-Chr4C_47059 and Novel-Chr4A_40498, while five LRR-RLK genes were targeted by Novel-Chr6B_65233 and Novel-Chr5D_60023, 19 PPR repeat proteins by Novel-Chr5C_57213 and Novel-Chr5D_58065. Our findings suggested that these miRNAs and cell wall-related genes played vital regulatory roles in the responses of sugarcane to cold stress. Overall, the results of this study provide insights into the transcriptional and post-transcriptional regulatory network underlying the responses of sugarcane to cold stress.